Chitin- and Chitosan-Based Biocomposites for Food Packaging Applications - Thomas, Sabu.; Jacob, Jissy; Loganathan, Sravanthi (Milton : CRC Press LLC, 2020)
Chitin is one of the most important biopolymers, synthesized by an enormous number of living organisms and is a promising bioactive polymer for food packaging applications due to its functional properties. This book focuses on composition, properties, characterization, and theoretical approach of chitin and chitosan bio-composites. It describes the most recent studies concerning chitin and chitosan-based films and gives an overview about future trends regarding the industrial applications of chitin and chitosan for food packaging purposes. This book is especially useful for researchers in the fields of bionanocomposites, especially those with an interest in packaging applications.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY / Engineering / Chemical & Biochemical; Food -- Packaging; Chitin